Perfusion index: Could this be a new triage tool for upper gastrointestinal system bleeding in the emergency department? A prospective cohort study - (:unkn) unknown (My University, 2021)
BACKGROUND: Many scoring systems for predicting mortality, rebleeding and transfusion needs among patients with upper gastrointestinal bleeding (UGIB) have been developed. However, no scoring system can predict all these outcomes. OBJECTIVE: To show whether the perfusion index (PI), compared with the Rockall score (RS), helps predict transfusion needs and prognoses among patients presenting with UGIB in emergency departments. In this way, critical patients with transfusion needs can be identified at an early stage. DESIGN AND SETTING: Prospective cohort study in an emergency department in Turkey, conducted between June 2018 and June 2019. METHODS: Patients' demographic parameters, PI, RS, transfusion needs and prognosis were recorded. RESULTS: A total of 219 patients were included. Blood transfusion was performed in 174 patients (79.4%). The PI cutoff value for prediction of the need for blood transfusion was 1.17, and the RS cutoff value was 5. The area under the curve (AUC) value for PI (AUC: 0.772; 95% confidence interval, CI: 0.705-0.838; P < 0.001) was higher than for RS (AUC: 0.648; 95% CI: 0.554-0.741; P = 0.002). 185 patients (84.5%) were discharged, and 34 patients (15.5%) died. The PI cutoff value for predicting mortality was 1.1, and the RS cutoff value was 7. The AUC value for PI (AUC: 0.743; 95% CI: 0.649-0.837; P < 0.001) was higher than for RS (AUC: 0.725; 95% CI: 0.639-0.811; P < 0.001). CONCLUSION: PI values for patients admitted to emergency departments with UGIB on admission can help predict their need for transfusion and mortality risk.
Keywords: Humans; Prognosis; Risk Assessment; Severity of Illness Index; Prospective Studies; ROC Curve; Gastrointestinal Hemorrhage; Emergency Service, Hospital; Triage; Perfusion Index